The The Realization of Refusal Strategies in Political Interviews Used by Donald Trump–The President of the United States of America - Ariyanti Rodiah, Hindria; Rukmini, Dwi; Mujiyanto, Januarius (Universitas Negeri Semarang, 2019)
Refusal is not simple to be taught to language learners. It is challenging act due to its intrinsically face threatening nature. This study is aimed at finding out the realization of refusal strategies in five different channels of political interviews used by Donald Trump–The President of United States of America. The method of collecting data is documentation. The researcher uses descriptive qualitative in analyzing the data. The results show that there are direct and indirect refusal strategies used by President Trump in five different channels of political interviews. In direct strategy, there are Ã¢â‚¬ËœnoÃ¢â‚¬â„¢ and negative willingness. Moreover, in indirect strategy, there are excuse reason and explanation, promise for future acceptance, statement of principle, threat or negative consequences, criticizing or statement of negative feeling or opinion, and verbal avoidance. Further, there are the similarities and differences of refusal strategies used by President Trump among the five different channels of political interviews. The similarities are shown in the interview with CNN; he is more indirect to refuse the interviewersÃ¢â‚¬â„¢ want. It is similar to the interview with FOX and CBS News that he is more indirect too. In addition, the differences are shown that in the interview with CNN, FOX, and CBS News, he uses more indirect refusal strategies. In contrast, in ABC and CNBC News, he uses more direct refusal strategies. In term of social status, he uses more of indirect refusal strategies to the interviewers who have lower social status. It means that he wants to soften the offending of interlocutorÃ¢â‚¬â„¢s face in refusals. This study also gives pedagogical implication for the language learners to improve their pragmatic competence especially in refusal speech act. Thus, they can use refusals appropriately for communication.